A Systematic Literature Review of Determinants Affecting Halal Food Purchasing Behaviour in the United Kingdom and France - Rachmadi Rizky Teja Kumara (Journal of Halal Review, 2025)
Objective: This study aims to identify and analyze the determinants of halal food purchasing behavior in Europe, particularly in the UK and France, with particular attention to the role of emotional values ​​compared to religiosity and social norms, which are more prevalent in Southeast Asia. Research Design & Methods: This study employed a Systematic Literature Review (SLR) approach, synthesizing academic studies published between 2000 and 2025 from databases such as Scopus, Web of Science, and ScienceDirect. A thematic analysis was conducted to examine cross-regional variations and highlight the unique drivers of halal consumption in European markets. Findings: The findings indicate that emotional values ​​emerge as the most significant determinant of halal food purchasing behavior in the UK and France. Unlike in Southeast Asia, where religiosity and social norms remain central, halal in Europe is increasingly understood as a marker of identity, ethical consumption, food quality, and universal moral values. Both Muslim and non-Muslim consumers view halal as a representation of trust, safety, sustainability, and modern lifestyle preferences, indicating a paradigm shift from religious adherence to broader ethical and emotional certainty. Implications & Recommendations: While detailed managerial strategies are beyond the scope of this paper, the results suggest that halal branding in Europe should focus on emotional and ethical dimensions, rather than solely religious certification. Positioning halal as an inclusive lifestyle choice associated with quality and universal values ​​is crucial for strengthening consumer loyalty and expanding global market penetration. Contribution & Value Added: This study contributes to the halal marketing literature by highlighting emotional value as a key determinant of consumer behavior in a Western context. It advances theory development in halal consumer studies by linking emotion, identity, and trust as interrelated factors in shaping purchase decisions. Furthermore, this study lays the foundation for future research exploring cross-regional comparisons and the role of digital platforms in strengthening emotional attachment to halal brands.